Relationship Between Maternal Dental Anxiety and Children’s Dental Caries in the Eastern Province of Saudi Arabia - Alhareky M; Nazir MA; AlGhamdi L; Alkadi M; AlBeajan N; AlHossan M; AlHumaid J (Dove Medical Press, 2021)
Muhanad Alhareky,1 Muhammad Ashraf Nazir,1 Lamia AlGhamdi,2 Mariam Alkadi,2 Noura AlBeajan,2 May AlHossan,2 Jehan AlHumaid1 1Department of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Muhammad Ashraf NazirDepartment of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, P. O. Box 1982, Dammam, 31441, Saudi ArabiaTel +966-38574928Email manazir@iau.edu.saPurpose: Dental anxiety is a barrier to dental care utilization and is associated with poor oral health outcomes. The aim of the study was to assess the relationship between dental anxiety of mothers and dental caries of their children in the Eastern Province, Saudi Arabia.Methodology: A cross-sectional study was conducted on a sample of mother–child pairs (N= 199) in Dammam, AlKhobar, and Dhahran, Saudi Arabia. Dental caries experience among children was determined using dmft/DMFT indexes following the World Health Organization’s guidelines. Maternal dental anxiety was assessed by using the Modified Dental Anxiety Scale (MDAS).Results: The mean ages of mothers and children were 33.98 ± 5.41 and 6.74 ± 2.29 years, respectively. The mean dmft score was 4.3 ± 3.99 in primary dentition and the mean maternal dental anxiety score was 13.89 ± 5.33. Ninety-two percent of mothers had low to extreme dental anxiety and only 8% reported no dental anxiety. Dental caries experience in primary teeth was higher in children of dentally anxious mothers (mean dmft 4.45 ± 3.92) than the children of mothers who were non-anxious (mean dmft 2.56 ± 4.59) (P=0.07). The mean maternal anxiety score was significantly higher in children with untreated decay in primary dentition (14.49 ± 5.08) than those with sound primary dentition (12.24 ± 5.67) (P = 0.008). The study also found a statistically significant correlation between maternal dental anxiety and untreated decay in the primary dentition (Pearson’s r =0.171, P = 0.015).Conclusion: Dental anxiety was highly prevalent among mothers in the present study. There was a significant relationship between maternal dental anxiety and untreated decay in the primary dentition. Awareness should be raised among dentally anxious mothers to reduce the burden of dental caries in their children.Keywords: caries, dental fear, access to oral care, children